Acceptability - a neglected dimension of access to health care: findings from a study on childhood convulsions in rural Tanzania - Dillip Angel; Alba Sandra; Mshana Christopher; Hetzel Manuel W; Lengeler Christian; Mayumana Iddy; Schulze Alexander; Mshinda Hassan; Weiss Mitchell G; Obrist Brigit (BMC, 2012)
Abstract Background Acceptability is a poorly conceptualized dimension of access to health care. Using a study on childhood convulsion in rural Tanzania, we examined social acceptability from a user perspective. The study design is based on the premise that a match between health providers' and clients' understanding of disease is an important dimension of social acceptability, especially in trans-cultural communication, for example if childhood convulsions are not linked with malaria and local treatment practices are mostly preferred. The study was linked to health interventions with the objective of bridging the gap between local and biomedical understanding of convulsions. Methods The study combined classical ethnography with the cultural epidemiology approach using EMIC (Explanatory Model Interview Catalogue) tool. EMIC interviews were conducted in a 2007/08 convulsion study (n = 88) and results were compared with those of an earlier 2004/06 convulsion study (n = 135). Earlier studies on convulsion in the area were also examined to explore longer-term changes in treatment practices. Results The match between local and biomedical understanding of convulsions was already high in the 2004/06 study. Specific improvements were noted in form of (1) 46% point increase among those who reported use of mosquito nets to prevent convulsion (2) 13% point decrease among caregivers who associated convulsion with 'evil eye and sorcery', 3) 14% point increase in prompt use of health facility and 4)16% point decrease among those who did not use health facility at all. Such changes can be partly attributed to interventions which explicitly aimed at increasing the match between local and biomedical understanding of malaria. Caregivers, mostly mothers, did not seek advice on where to take an ill child. This indicates that treatment at health facility has become socially acceptable for severe febrile with convulsion. Conclusion As an important dimension of access to health care 'social acceptability' seems relevant in studying illnesses that are perceived not to belong to the biomedical field, specifically in trans-cultural societies. Understanding the match between local and biomedical understanding of disease is fundamental to ensure acceptability of health care services, successful control and management of health problems. Our study noted some positive changes in community knowledge and management of convulsion episodes, changes which might be accredited to extensive health education campaigns in the study area. On the other hand it is difficult to make inference out of the findings as a result of small sample size involved. In return, it is clear that well ingrained traditional beliefs can be modified with communication campaigns, provided that this change resonates with the beneficiaries.